2012
DOI: 10.1016/j.jnutbio.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and epigenetics: an interplay of dietary methyl donors, one-carbon metabolism and DNA methylation

Abstract: DNA methylation is the most extensively studied mechanism of epigenetic gene regulation. Increasing evidence indicates DNA methylation is labile in response to nutritional and environmental influences. Alternations in DNA methylation profiles can lead to changes in gene expression, resulting in diverse phenotypes with the potential for increased disease risk. The primary methyl donor for DNA methylation is S-adenosylmethionine (SAM), a species generated in the cyclical cellular process called one-carbon metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
467
2
31

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 631 publications
(505 citation statements)
references
References 62 publications
5
467
2
31
Order By: Relevance
“…Together with B12, folic acid is an important methyl donor which is crucial for fetal development (Zeisel, 2009) and it seems to be important in DNA methylation, being associated with cancer prevention (Anderson, Sant, & Dolinoy, 2012). Liver, especially from pigs, is a great source of folic acid supplying 81% of DR while calf liver supplies 87% of DR.…”
Section: Other Vitamins -Vitamin a Folic Acid Zinc And Seleniummentioning
confidence: 99%
“…Together with B12, folic acid is an important methyl donor which is crucial for fetal development (Zeisel, 2009) and it seems to be important in DNA methylation, being associated with cancer prevention (Anderson, Sant, & Dolinoy, 2012). Liver, especially from pigs, is a great source of folic acid supplying 81% of DR while calf liver supplies 87% of DR.…”
Section: Other Vitamins -Vitamin a Folic Acid Zinc And Seleniummentioning
confidence: 99%
“…An exciting discovery was the demonstration that nutrients influence gene function by interacting with nuclear receptors (vitamins A and D) and also through epigenetic mechanisms (folate, vitamin B 12 , etc.) (Anderson et al, 2012). Both mechanisms modulate gene expression.…”
Section: Nutrition and Foetal Programmingmentioning
confidence: 99%
“…The 5-methylTHF is used in the one-carbon metabolism cycle by donating its methyl group to homocysteine, converting it to methionine (Eto et al, 1986;Beetstra et al, 2005) and by that, replenishing cellular SAM (Caudill et al, 2001;Fenech, 2001;Anderson et al, 2012). This favours the increase in the dUMP pool and promotes an even bigger uracil incorporation into DNA.…”
Section: )mentioning
confidence: 99%
“…Many current studies use a candidate gene-specific approach to examine the effects of folate on DNA methylation. The selected genomic loci are usually linked with a disease outcome of interest (in preventative or therapeutic strategies) such as cancer or diabetes, and these studies usually explore folate's role in methylation of target tissue types (Anderson et al, 2012). Similarly, a cohort study in Netherlands showed that low-folate intake combined with high alcohol consumption resulted in non-significant changes in gene promoter methylation in blood of CRC patients (Van Engeland et al, 2003).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation